Designing Infographics to Disseminate Information on Sea Turtle Conservation at Sekolah Alam of BSTC - Radhitanti, Asri; Kusumawati, Yudhistya Ayu; Pranoto, Christoforus Justine; Lasmy, Lasmy (Lembaga Dongan Dosen, 2024)
Sekolah Alam represents one of Bajulmati Sea Turtle Conservation (BSTC) inisiatives to disseminate knowledge through education and training regarding sea turtle conservation to a broader audience. This programme is conducted at the Bajulmati Beach conservation area, which has been developed into several ecotourism sites. Those participating in the programme will gain insight into the benefits of conservation and the importance of protecting sea turtles and their habitats. Following the site observation to the conservation area of this community service programme, it was identified that the education and training materials on sea turtle conservation in the form of posters, guidebook, and oral delivery method, represented a significant concern. Prior research has indicated that the use of infographics, or information graphics, has become a popular method of disseminating information, particularly when the subject of the information is complex. Infographics have been employed in various fields, and are even highly recommended for use in the context of learning and information dissemination. Consequently, the utilisation of infographics in addressing visual communication challenges encountered in this community service programme, in the field of ecotourism, should also be effective. This article outlines the design process of the infographics, which will serve as a supporting medium for the facilitation of learning and transfer of information about sea turtle conservation at Sekolah Alam of BSTC.